Dynamic ERK signaling regulation in intestinal tumorigenesis. (3rd September 2018) - Muta, Yu; Matsuda, Michiyuki; Imajo, Masamichi
ABSTRACT: Extracellular signal-regulated kinase (ERK) plays a critical role in tissue homeostasis and tumorigenesis. By utilizing live imaging approaches, we recently uncovered ERK activity dynamics in the intestinal epithelium. Notably, we showed that ERK activity dynamics are defined by composite regulation from two distinct upstream receptors, and alteration of their functional balance underlies tumor cell-specific traits. Here, we discuss these findings.